Motivations Behind the Exposure of Academic Elites to Iraqi Sports Television Program Pages on Social Media and the Gratifications Achieved - Sayhood, Dr. Anmar Ghafil (Thi Qar Arts Journal, 2025)
In the contemporary digital landscape, all segments of society - including university professors - are increasingly engaging with social media platforms, particularly sports-related pages. This study addresses a key research problem: understanding the motivations driving this engagement and exploring its implications in depth. The study investigates how academic elites interact with sports program pages on social media and seeks to answer the following core research questions: • Which television program pages are most preferred by academic elites? • To what extent do sports programs contribute to enhancing audience gratification? • What is the role of sports program pages in promoting athletic achievement? The study aims at: • Examining the patterns of audience exposure to sports-related pages. • Assessing the contribution of sports programs in fulfilling audience gratifications. • Exploring the role of sports-related pages in enhancing sports performance and achievement. The research population includes 80 male and female faculty members from the Colleges of Physical Education in Karbala. The sample was selected using a purposive sampling method, in alignment with scientific methodology, to ensure precise and reliable data collection for analysis. The study yielded the following significant results: • The majority of the academic faculty reported viewing sports program pages primarily through Facebook. • Academic elites typically consume content at home and frequently discuss program topics with peers and colleagues. • The most preferred program among respondents was "Hattrick", aired on the UTV channel, which ranked significantly higher in popularity compared to other sports programs. Based on the findings, the researcher recommends the following: • Television sports programs should be designed to include purposeful and developmental content that contributes to the growth of the sports sector in Iraq. Moreover, such programs should feature analysts and experts who offer balanced and unbiased commentary, avoiding defamatory or politically charged discourse. • Diverse sports coverage should be prioritized. Programs ought to cover a broad range of sports - both team-based and individual - rather than focusing predominantly on football, even though it attracts a large viewership.